Effect of sulfur poisoning on the performance and active sites of Cu/SSZ-13 catalyst. (23rd November 2020) - Jiang, Han; Guan, Bin; Peng, Xuesong; Wei, Yanfei; Zhan, Reggie; Lin, He; Huang, Zhen
Graphical abstract: Highlights: The impact of sulfur poisoning and regeneration on Cu/SSZ-13. Regeneration could not totally recover the efficiency of sulfured catalysts. Different sulfate species formed on the main active sites of Cu/SSZ-13. SO2 was oxidized by Cu x O y species, and Si-O(H)-Al bond could not be poisoned without active metal species. Active sites and nitrates/nitrites storage capacity decreased after sulfur poisoning. Abstract: This study focuses on exploring the impact of sulfur poisoning and regeneration on the performance and active sites of Cu/SSZ-13 catalyst. It was found that sulfured samples had obviously lower conversion than fresh samples below 350 °C, and thermal regeneration at 550 °C could not totally remove sulfate species. These catalysts were also comprehensively characterized by H2 -TPR, TPD, NH3 -TPO, NO-TPO, and BET. SO2 and NH3 co-adsorbed on the Z2 Cu sites to form ammonia sulfate species, however, they went through the two-step decomposition reaction during regeneration. SO2 interacted more tightly with ZCuOH to form copper bisulfite species. SO2 was oxidized by Cu x O y species to further form sulfate species. Si-O(H)-Al bond could be sulfur poisoned when Cu species in the catalysts. Additionally, sulfated species could block pores, but not lead to structure collapse. Furthermore, in situ DRIFTS results illustrated that active sites and nitrates/nitrites storage capacity decreased after sulfur poisoning.